Potential use of black soldier fly, Hermetia illucens larvae in chicken feed as a protein replacer: a review - Zaid, M. Z. A.; Ramiah, S. K.; Jamein, E. S.; Zulkifli, I.; Lokman, I. H.; Amirul, F. M. A.; Fadzlin, S. A. A.; Mohd Zamri, S.; Jayanegara, A.; Hassim, H. A. (Kielanowski Institute of Animal Physiology and Nutrition, Polish Academy of Sciences in Jabłonna, 2023)
The increasing human population and improved living standards in developing countries have led to a higher demand for animal proteins, which has resulted in increased costs of animal feed ingredients such as fish meal, fish oil, soybean meal, and cereals. The global economic slowdown, has further compounded this challenge, making it crucial for the animal production industry to find innovative methods to secure future social, environmental and economic needs. Black soldier fly (BSF) larvae have emerged as a promising nutrient alternative due to their high protein and fat contents and a rich source of vitamins and minerals comparable to soybean and fish meal. Black soldier fly larvae (BSFL) has the potential to reduce the cost of chicken feed formulations by partially replacing soybean and/or fish meals. This is one of the primary reasons why insects like BSF are seen as viable alternative protein sources for animal feeds. This review attempts to assess the challenges faced by the poultry industry and strategies to overcome feeding issues through the use of BSFL.